The unique disarticulation layer formed in the rachis of Aegilops longissima probably results from the spatial co-expression of Btr1 and Btr2. (7th August 2020) - Zeng, Xiaoxue; Chen, Gang; Wang, Lei; Tagiri, Akemi; Kikuchi, Shinji; Sassa, Hidenori; Komatsuda, Takao
Abstract: Background and Aims: The brittle rachis trait is a feature of many wild grasses, particularly within the tribe Triticeae. Wild Hordeum and Triticum species form a disarticulation layer above the rachis node, resulting in the production of wedge-type dispersal units. In Aegilops longissima, only one or two of the nodes in the central portion of its rachis are brittle. In Triticeae species, the formation of a disarticulation layer above the rachis node requires the co-transcription of the two dominant and complementary genes Btr1 and Btr2 . This study aims to establish whether homologues of Btr1 and/or Btr2 underlie the unusual brittle rachis phenotype observed in Ae. longissima . Methods: Scanning electron microscopy was used to examine the disarticulation surfaces. Quantitative RT-PCR and RNA in situ hybridization experiments were used to identify gene expression in the immature inflorescence. Key Results: Analysis based on scanning electron microscopy was able to demonstrate that the disarticulation surfaces formed in the Ae. longissima rachis are morphologically indistinguishable from those formed in the rachises of wild Hordeum and Triticum species. RNA in situ hybridization showed that in the immature Ae. longissima inflorescence, the intensity of Btr1 transcription varied from high at the rachis base to low at its apex, while that of Btr2 was limited to the nodes in the central to distal portion of the rachis. Conclusions: The disarticulation pattern shown by Ae. longissima results from the limitation of Btr1 and Btr2 co-expression to nodes lying in the centre of the rachis.